The Effect of β-Glucan on the Release and Antiradical Activity of Phenolic Compounds from Apples in Simulated Digestion - Lidija Jakobek; Daniela Kenjerić; Lidija Šoher; Petra Matić (Molecules)
Beneficial activities of phenolic compounds in the gastrointestinal tract, such as antiradical activity, are affected by the food matrix. The aim of this study was to investigate the influence of one constituent of the food matrix (dietary fiber β-glucan) on the release and antiradical activity of phenolic compounds from apples in gastrointestinal digestion. Simulated digestion in vitro was conducted on whole apples without or with added β-glucan. Antiradical activity was determined with the DPPH method. The total amount of released phenolic compounds in the stomach (563 mg kg−1 fresh weight (fw), 85%) decreased in the intestine (314 mg kg−1 fw, 47%) (p < 0.05). The presence of β-glucan decreased the release of phenolic compounds to 80 and 74% in the stomach and to 44 and 40% in the small intestine when there were lower and higher β-glucan amounts, respectively. A statistical analysis showed differences between release in digestion without or with β-glucan. B-glucan adsorbed up to 24 (stomach) and 32 mg g−1 (small intestine) of the phenolics. Phenolic compounds scavenged more free radicals in the small intestine than in the stomach, and β-glucan decreased this activity, but not significantly. The interaction between β-glucan and phenolic compounds should be considered when explaining the beneficial effects in the stomach and small intestine.